FORMULASI SABUN TRANSPARAN BERBASIS MINYAK KELAPA MURNI (VCO) - Ropiqa, Meri; Azmi, Khulul; Septina, Diani Ria (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
VCO has been widely used as a base of soap formulation. It was used due to its high fatty acid contain resists to oxidation causing stinky smell. The highest abundant of fatty acid in VCO was reported as lauric acid (52%). Lauric acid was known contribute to moisturize the skin. Hence widely used as a base of soap manufacture. The type of soap formulate in this study was the transparent soap due its appealing appearance. To find the best formulation of transparent soap according to SNI. Methods: transparent soap was formulated using hot process technique with two different concentrations of VCO which were 20% and 30%. The obtained soaps were then tested using SNI criteria such as organoleptic, pH, foam stability, and fatty acid. According to T-test, it was resulted p value>0,05 showing those two formulation did not have significance differentiation on pH test and foam stability test. The fatty acid concentration test of those two formulation showed different result significantly but it was still fulfilling the SNI requirement (≤ 2,5%). The formulas obtained of transparent soap using VCO as the base was known fulfill the quality standard of SNI.